Nodular Fasciitis of the Breast - Moghimi, Mansour (Iran J Radiol, 2016)
Nodular fasciitis of the breast is a rare benign pathology of soft tissue that is a consequence of fibroblastic hyperplasia within breast. It can mimic breast cancer clinically, radiologically, and histopathologically. A-43 year-old female with a painless mass within upper-lateral quadrant of her left breast complained of rapid and progressive growth during previous few days. No evidence of nipple discharge or sensation of pain was expressed. The mass was tender to palpation, but the size was too tiny to detect. The definitive diagnosis was established with sonography, which detected a hypoechogenic lesion, 10 mm in diameter. The excisional biopsy delivered a tissue composed of fusiform fibroblastic cells with bright ellipsoid-like nuclei and elevated nucleolus. Mitotic formations were also obvious. Low cellular and high cellular zones with hyaline fibrosis and erythrocyte accumulation existed, as well as a light lymphocytic infiltration. All of these features, in addition to adipocytic accumulation within the margins of this lesion, suggested a definitive diagnosis of Nodular fasciitis. The diagnosis of nodular fasciitis is difficult and often is indiscriminable from breast cancer, so paying close attention to this matter is critical.